PROSES PENYEMBUHAN LUKA ULKUS DIABETIKUM DENGAN METODE MODERN DRESSING DIKLINIK MAITIS EFRANS WOUND CARE - Nabila, Nadya Putri; Husni, Pauzan Efendi, (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
Diabetes mellitus (DM) is one of the most common chronic diseases experienced by the world population and ranks fourth cause of death in developing countries. Long-term complications of diabetes mellitus one of them is diabetic ulcer (15%) and is the most cause (85%) of amputation in patients with diabetes mellitus. Currently, more than 5,000 modern types of dressings are reported to be available to treat wounds, especially diabetic ulcers. To know the process of wound healing diabetic ulcer was done with the design of case study research with a sample of 2 people and this study was conducted for 4 weeks. The study was conducted at the Maitis Efrans Wound Care clinic in Bengkulu City. The result was obtained that the assessment of diabetic ulcer wounds before modern wound care on the respondents was a total score of 54 and the respondents two total score of 50 were stated wound regeneration. The healing process of the responder's second ulcers progressed, the total score of one respondent was 30 and the respondent two was 28. Respondents. Progress on the two respondents stated better influenced by wound healing factor that is, age factor.